KEPEMIMPINAN KEPALA DESA DALAM PEMBERDAYAAN MASYARAKAT ( STUDI DI DESA RAMBAH MUDA KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU) TAHUN 2021 - Cindy Oktaviani; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The leadership of the village head is a determinant of the direction for the progress or decline of the village itself. The empowerment carried out in the village does not only involve the village head, but also the involvement of the community and village apparatus. The village head has the task of empowering the village community whose goal is the welfare and independence of the village in its economy. Village head leadership is a way of moving and influencing other people (community or village apparatus). The method used is a qualitative method, the theory used in explaining this research is Kartono's leadership theory. Data collection techniques using interviews and documentation. The type of data in this study is primary data in the form of data obtained from research informants and secondary data obtained from related documents. The results of this study indicate that the village head's leadership is something that is really needed by the people of Rambah Muda Village in implementing empowerment whose goal is to improve the welfare and independence of the village. Communication, responsibility, activeness of leaders, and motivation are the ways that the village head does in increasing community empowerment in Rambah Muda Village, especially in empowering food security and agricultural training. Based on these 4 indicators, it can be seen that the leadership of the Head of Rambah Muda Village in implementing food security empowerment in Rambah Muda Village can be said to be quite good. This can be seen from the village head's ability to establish communication by providing information to Farmer Groups, being responsible for carrying out his duties to develop the potential of idle land villages so that they can be empowered which is carried out in the food security program, being active in providing understanding to farmer groups through Agricultural Extension officers Field (PPL) by conducting training and providing good motivation to Farmer Groups. Keywords: Village Head Leadership, Empowerment